2020
DOI: 10.1242/jeb.216762
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of mitochondrial respiration in permeabilized fish gills

Abstract: Physiological investigations of fish gills have traditionally centred on the two principal functions of the gills: gas exchange and ion regulation. Mitochondrion-rich cells (MRCs) are primarily found within the gill filaments of fish, and are thought to proliferate in order to increase the ionoregulatory capacity of the gill in response to environmentally induced osmotic challenges. However, surprisingly little attention has been paid to the metabolic function of mitochondria within fish gills. Here, we descri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…Salin et al, 2016), but this was an expected outcome since adipose tissue is mostly composed of lipids (Nanton et al, 2007). Despite the lower rate of mitochondrial respiration in adipose tissue, the L/P ratio indicated that approximately 30% of mitochondrial respiration was related to proton leak, which is similar to the levels reported previously in fish intestine (Brijs et al, 2017), but higher than that reported in gill (Dawson, Millet, Selman, & Metcalfe, 2020), or muscle and liver (Salin, Auer, Anderson, Selman, & Metcalfe, 2016), though it should be noted that the protocols used in measuring Leak respiration often differ between studies. As expected, CI&CII-linked respiratory leak through the entire electron transport chain (Leak Omy) was higher than CI-linked respiratory leak (Leak CI) in our study.…”
Section: Discussionsupporting
confidence: 84%
“…Salin et al, 2016), but this was an expected outcome since adipose tissue is mostly composed of lipids (Nanton et al, 2007). Despite the lower rate of mitochondrial respiration in adipose tissue, the L/P ratio indicated that approximately 30% of mitochondrial respiration was related to proton leak, which is similar to the levels reported previously in fish intestine (Brijs et al, 2017), but higher than that reported in gill (Dawson, Millet, Selman, & Metcalfe, 2020), or muscle and liver (Salin, Auer, Anderson, Selman, & Metcalfe, 2016), though it should be noted that the protocols used in measuring Leak respiration often differ between studies. As expected, CI&CII-linked respiratory leak through the entire electron transport chain (Leak Omy) was higher than CI-linked respiratory leak (Leak CI) in our study.…”
Section: Discussionsupporting
confidence: 84%
“…This is in line with our measurements of Na + /K + -ATPase activity and also of V-ATPase activity in gill tissue and ABO, which revealed that the activity of both ATPases compared to activities recorded in water breathing fish or even the air-breathing Hoplerythrinus unitaeniatus are particularly low, pointing to a low ion exchange capacity of A. gigas gills, in small as well as in larger fish [8,27]. In accordance, the gills' oxygen uptake of A. gigas is lower compared to the water-breathing brown trout (Salmo trutta) [28]. Interestingly, the RCR of gills of larger fish is greater than that of small fish.…”
Section: Plos Onementioning
confidence: 68%
“…In accordance, the gills' oxygen uptake of A . gigas is lower compared to the water-breathing brown trout ( Salmo trutta ) [ 28 ]. Interestingly, the RCR of gills of larger fish is greater than that of small fish.…”
Section: Discussionmentioning
confidence: 99%
“…This article is protected by copyright. All rights reserved respiration protocols to determine LEAK (Ln) and respiratory control ratio (RCR) were adapted from Dawson, Millet et al (2020), for details see ESM 3.…”
Section: Accepted Articlementioning
confidence: 99%
“…Respiration rate was measured as the rate of decline in O 2 concentration. Mitochondrial respiration protocols to determine LEAK (Ln) and respiratory control ratio (RCR) were adapted from Dawson, Millet, et al (2020), for details see ESM 3.…”
Section: Mitochondrial Metabolismmentioning
confidence: 99%